2012
DOI: 10.1111/j.1601-6343.2012.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pre‐surgical infant orthopedic treatment for cleft lip and palate patients: a systematic review and meta‐analysis

Abstract: The objective of the study was to systematically summarize current evidence on the effectiveness of pre-surgical infant orthopedics (PSIO) in cleft lip and palate (CLP) patients. Electronic and manual searches were conducted, and using specific inclusion and exclusion criteria, data extraction and analysis was performed by two independent investigators. When possible, overall pooled estimates with 95% confidence intervals were obtained using the random-effects model. Twenty-four of 885 original studies met the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 81 publications
(266 reference statements)
2
45
0
5
Order By: Relevance
“…Two recent systematic reviews concluded that existing evidence cannot support the short- or long-term effectiveness of IO in UCLP patients due to the variety of treatment outcomes in RCTs, small sample sizes, and missing information on sample selection [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Two recent systematic reviews concluded that existing evidence cannot support the short- or long-term effectiveness of IO in UCLP patients due to the variety of treatment outcomes in RCTs, small sample sizes, and missing information on sample selection [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…The available empirical evidence suggests that intervention effects in orthodontic research seem to differ in non-RCTs compared to RCTs [72]. The two systematic reviews published recently that evaluated PSIO appliances in general [11, 12], also included non-RCTs. Furthermore, neither attempted to summarize the quality of available evidence and thus provide an insight into the strength of the relevant recommendations, as was carried out in the present systematic review based in the GRADE approach [20].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly however, this practice still remains a subject of controversy [9]. Two systematic reviews evaluating PSIO in general [10, 11], and one assessing growth and development outcomes after various feeding interventions in infants with cleft lip and/or palate [12] have been published recently. However, neither of these attempted to summarize the available quality of evidence and thus provide an insight into the strength of the relevant recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…c Mit 6 Monaten. Für diese Effekte gibt es nach heutigem Stand der Forschung -außer einer vorübergehenden Verbesserung der Sprache -keine Evidenz für eine Verbesserung der Behandlungsergebnisse [23,24].…”
Section: Allgemeines Zur Therapieunclassified